Youth Attitudes Towards Goals of a New Sustainable Development Agenda - Borojević, Tatjana; Maletič, Matjaž; Petrović, Nataša; Radaković, Jelena Andreja; Senegačnik, Marjan; Maletič, Damjan (Problemy Ekorozwoju, 2017)
The whole world adopted a global strategy as the only possible one – a global development strategy based on the principles of sustainability. This strategy includes not only all types of politics, economies and societies, but is also an integral part of life and wellbeing of all people. A new sustainable development agenda for the period 2015-2030 identifies youth not only as a category much more sensitive to sustainability, but in each of its 17 goals of sustainable development emphasizes the role of young people and the need for their active participation in the promotion and realization of these objectives and its targets. Bearing this in mind, the research presented in the paper deals with young people’s knowledge on sustainable development, the strategy of sustainable development, and their attitudes towards the goals of sustainable development in the context of what they themselves find most important. Obtained results in the case study of the Republic of Serbia, not only show the results of the analysis of young people’s viewpoints on these crucial issues but also of a good way to continue research in this area not only by the authors of the paper but other researchers who are engaged in activism and participation of youth in sustainable development as well.